Inorganic mercury exposure toxicological effects, oxidative stress biomarkers and bioaccumulation in the tropical freshwater fish matrinxã, Brycon amazonicus (Spix and Agassiz, 1829) - Monteiro, Diana Amaral (Ecotoxicology (London, England), 2010)
Alterations in the antioxidant cellular system have often been proposed as biomarkers of pollutant-mediated toxicity. This study evaluated the effects of mercury on oxidative stress biomarkers and bioaccumulation in the liver, gills, white muscle and heart of the freshwater fish matrinxã, Brycon amazonicus, exposed to a nominal and sub-lethal concentration (~20% of 96 h-LC(50)) of 0.15 mg L(-1) of mercury chloride (HgCl(2)) for 96 h in a static system. Increases in superoxide dismutase, catalase, glutathione peroxidase (GPx), glutathione S-transferase (GST) and glutathione reductase (GR) were observed in all tissues after HgCl(2) exposure, except for white muscle GR activity and hepatic GPx. In the liver and gills, the exposure to HgCl(2) also induced significant increases in reduced glutathione (GSH). Conversely, exposure to HgCl(2) caused a significant decrease in the GSH levels and an increase in the oxidized glutathione (GSSG) content in the white muscle, while both GSH and GSSG levels increased significantly in the heart muscle. Metallothionein concentrations were significantly high after HgCl(2) exposure in the liver, gills and heart, but remained at control values in the white muscle. HgCl(2) exposure induced oxidative damage, increasing the lipid peroxidation and protein carbonyl content in all tissues. Mercury accumulated significantly in all the fish tissue. The pattern of accumulation follows the order gills > liver >> heart > white muscle. In conclusion, these data suggest that oxidative stress in response to inorganic mercury exposure could be the main pathway of toxicity induced by this metal in fish